Thrombocytopenia in pregnant women with severe preeclampsia and eclampsia - Alva, José (2015)
OBJECTIVE: To determine the incidence of thrombocytopenia in severe pre-eclampsia and eclampsia, in relation to material age, gestational age and parity. DESIGN: Basic, descriptive and porspective study performed at Trujillo Teaching Regional Hospital between april 1, and december 1, 1995. PACIENTES: 45 preeclamptic, severe, and eclamptic women with ³ 28 weeks gestational age. RESULTS: Thrombocytopenia was found in 48,8% without significant differences in regards to maternal age, gestational age and parity. CONCLUSION: thrombocytopenia was found in almost half of pregnancy induced hypertension patients.